(R)‐ and (S)‐ketamine induce differential fMRI responses in conscious rats. Issue 12 (5th September 2019) - Masaki, Yukiko; Kashiwagi, Yuto; Watabe, Hiroshi; Abe, Kohji
Abstract: (R, S)‐ketamine exerts robust antidepressant effects in patients with depression when given at sub‐anesthetic doses. Each of the enantiomers in this racemic mixture, (R)‐ketamine and (S)‐ketamine, have been reported to exert antidepressant effects individually. However, the neuropharmacological effects of these enantiomers and the mechanisms underlying their antidepressive actions have not yet been fully elucidated. Therefore, we investigated the effect of (R, S)‐, (R)‐, and (S)‐ketamine on brain activity by functional MRI (fMRI) in conscious rats and compared these with that of N‐methyl‐D‐aspartate receptor (NMDAR) antagonist MK‐801 ( n  = 5~7). We also assessed their pharmacokinetic profiles ( n  = 4) and their behavioral effects ( n  = 7~9). This pharmacological MRI study revealed a significant positive response to (S)‐ketamine specifically in the cortex, nucleus accumbens and striatum. In contrast, negative fMRI responses were observed in various brain regions after (R)‐ketamine administration. (R, S)‐ketamine, evoked significant positive fMRI responses specifically in the cortex, nucleus accumbens and striatum, and this fMRI response pattern was comparable with that of (S)‐ketamine. MK‐801‐induced similar fMRI response pattern to (S)‐ketamine. The fMRI responses to (S)‐ketamine and MK‐801 showed differential temporal profiles, which corresponded with brain concentration profiles. (S)‐ketamine and MK‐801 significantly increased locomotor activity, while (R)‐ketamine produced no noticeable change. (R, S)‐ketamine tended to increase locomotor activity. Our novel fMRI findings show that (R)‐ketamine and (S)‐ketamine induce completely different fMRI response patterns on rat, and that the response produced by the latter is similar to that elicited by an NMDAR antagonist. Our findings provide insight into the antidepressant mechanism of (R, S)‐ketamine. Abstract : Our fMRI study shows that (R)‐ketamine and (S)‐ketamine, each of the enantiomers in (R, S)‐ketamine, induce completely different fMRI response patterns on rat, and that (S)‐ketamine, but not (R)‐ketamine, elicits NMDAR antagonist‐like brain activation. Our novel findings provide insight into the antidepressant mechanism of (R, S)‐ketamine.